PENGARUH PENGAWASAN, PEMBERIAN INSENTIF FINANCIAL DAN PEMBERIAN INSENTIF NON FINANCIAL TERHADAP KINERJA KARYAWAN PADA KARAOKE VENUS - Nurrofi, Akhmad (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
This study aims to examine and analyze the influence ofSupervision, Financial Incentives and Provision of Non FinancialIncentives to (Employee Performance). Data was collected throughquestionnaires and implemented on 40 employees and this study usedSPSS version 17.The result of analysis shows that the first equation is Y = -5.066 +0,488.X1 + 0,254. X2 + 0.464. X3 which means supervisory variables,Financial Incentive Incentives and Non-Financial Incentives have apositive effect on employee performance variables..